United Republic of Tanzania : Third Review Under the Policy Support Instrument; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Tanzania. (IMF Staff Country Reports; Country Report, 2008)
Tanzania's performance ranks among the best for non-oil exporting countries in sub-Saharan Africa. The 2008/09 budget will aim at maintaining hard-won fiscal stability in the face of large spending needs and uncertain financing. Tighter budget constraints highlight the need to further expand the revenue base and achieve greater efficiency and effectiveness of government spending. Building on its recent success of reining in reserve money growth, the Bank of Tanzania (BoT) will aim to gradually bring down inflation to its medium-term objective of 5 percent.